A Pemetaan Sosio Kultural Mad'u dan Pengembangan Dakwah Kota Gorontalo - Andries Kango (Al-Ulum, 2020)
This paper focuses on the socio-cultural mapping of the Mad'u in Gorontalo and the development of its da'wah. This study employs qualitative research with sociological, cultural, and da'wah approaches that were applied using interviews, observations, and documentation of the sub-district or village government, Da'i, religious leaders, and selected communities. Empirical data shows that da'wah institutions in Gorontalo City do not have da'wah maps. The da'wah that is carried out is instant, monotonous, temporary, and not based on the development plan document. Findings; This study found the socio-cultural characteristics of the people of Gorontalo Municipality, consisting of industrial and agricultural communities. The development of this preaching is focused on the ahsan al-'amal approach and continuing to defend the ahsan al-qaul. The form of da'wah is tablig, tadbir, tatwir, and irshad. The activities are in the form of ta'lim, taujih, mau'izah, nasihah, irsyad, tadbir, and tatwir.